Variation in women’s attitudes toward intimate partner violence across the rural-urban continuum in Ethiopia - Amare, Mulubrhan; Arndt, Channing; Guo, Zhe; Seymour, Greg (International Food Policy Research Institute, 2020)
Little is known about the impacts of urbanization on women’s attitudes toward intimate partner violence (IPV). The scarcity of empirical studies on this relationship can be partly attributed to the lack of an objective measure of urbanization levels. In this study, we investigate the effects of urbanization on both women’s attitudes toward IPV using three continuous measures of urbanization: nightlight intensity, distance to urban areas, and total urban area within a 10-km radius. These measures are defined from satellite-based nighttime-light-intensity and multispectralsensor data. We find that despite a generally strong positive association between urbanization and progressive attitudes among women toward IPV, some stages of urbanization show a more significant association than others. Such nonlinear relationships are apparent in all estimations and across different measurements of urbanization. The heterogeneities in the effect of urbanization on women’s attitudes toward intimate partner violence further show that the effects of urbanization are sharply heterogeneous across wealth indicator terciles. While we find that urbanization is associated with an overall decrease in the acceptance of IPV, the effect is mostly concentrated in higher wealth terciles. For women in lower wealth terciles, urbanization is either insignificant or even associated with an increase in the acceptance of IPV.